DAMPAK MOTIVASI DAN KOMPETENSI TERHADAP PRESTASI KERJA DIMEDIASI OLEH GAYA KEPEMIMPINAN (STUDI EMPIRIS PENDEKATAN STRUCTURAL EQUATION MODELLING) - HERY SYAHRIAL (LP2MTBM MAKARIOZ, 2020)
The purpose of this research is to find out the impact of employee work motivation and competence that employees have onwork performance by paying attention to leadership style relationships. The sample taken in this study was as many as 118employees of retail companies spread in Medan Polonia sub-district. The analysis technique used is Structure EquationModelling (SEM). The study concluded that employee motivation will positively and significantly affect managementleadership styles, but competencies have no significant negative effect on leadership style. Work motivation proved to havean insignificant effect on employees' work performance. Competency positively and significantly af